1977
DOI: 10.1126/science.867052
|View full text |Cite
|
Sign up to set email alerts
|

Freeze-Fractured Purple Membrane Particles: Protein Content

Abstract: Optical diffraction and image reconstruction can be used to correlate the electron microscope image of the biological membrane with its electron density projection. Such correlation shows that a single purple membrane particle contains 9 to 12 protein molecules--63 to 84 transmembrane alpha helices--a complexity two to ten times greater than that previously suggested for membrane particles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

1977
1977
1989
1989

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(31 citation statements)
references
References 25 publications
0
31
0
Order By: Relevance
“…It seems likely that any such detail is destroyed by plastic deformation during freeze-fracturing of thylakoids, although it is thought that this deformation is less extensive in membranes where complementarity between the EF and PF faces is preserved (14,22). Such fine structure has been reported for rotary shadowed particles of the PF face of the red blood cell membrane (26), but it is not clear to what extent it is caused by decoration, particularly under conditions of low shadow angle and a thin coating of platinum.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It seems likely that any such detail is destroyed by plastic deformation during freeze-fracturing of thylakoids, although it is thought that this deformation is less extensive in membranes where complementarity between the EF and PF faces is preserved (14,22). Such fine structure has been reported for rotary shadowed particles of the PF face of the red blood cell membrane (26), but it is not clear to what extent it is caused by decoration, particularly under conditions of low shadow angle and a thin coating of platinum.…”
Section: Discussionmentioning
confidence: 99%
“…The molecular composition of light-harvesting complex particles has not been determined. However, a correlation between the size of freeze-fracture particles in the purple membrane of Halobacterium halobium and the electron diffraction map of this membrane has shown that each particle of 120 A diameter consists of several polypeptides, with a total molecular weight of about 300,000 (14). It is not valid to make a direct comparison between this membrane and light-harvesting complex liposomes since sufficient data are not yet available, but light-harvesting complex particles may contain about eight molecules of the light-harvesting chlorophyll a/b-protein, each of which contains approximately 14 molecules of chlorophyll (9).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…0105-1938/80/0045/0201/$ 02.00 useful to know the precise size of these freezefracture particles in order to calculate their molecular weight, and to correlate this with their polypeptide composition (see 6). Since most studies have employed uni-directionally shadowed replicas, it has only been possible to obtain an average value for particle size from their size distribution, and it has been assumed that these particles have a circular cross-section at the freeze-fracture plane (2).…”
Section: )mentioning
confidence: 99%
“…' Although it has been assumed that the lymphocyte IMP are mainly proteins that span the membrane (3, 4), it may well be that the large majority of lymphocyte transmembrane proteins are not revealed as IMP by the freeze-fracture technique, possibly because they do not form molecular aggregates of large enough size (9) .…”
mentioning
confidence: 99%